Effects of Various Calcination Times and Temperatures on Zinc Oxide as Gas Sensing For Volatile Organic Compound - ABDULLAH, SURAINI; AINUDDIN@NORDIN , AINUN RAHMAHWATI (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The investigation aimed to analyze the impact of varying calcination temperatures on the structural, morphological, and elemental properties of ZnO nanostructures synthesized via a hydrothermal approach. Nine distinct samples denoted as A1, A2, A3, B1, B2, B3,C1, C2, and C3 were synthesized at temperatures of 400ºC, 500ºC, and 600ºC, each for intervals of 0, 2, and 4 hours. A comprehensive analysis was conducted employing X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and energydispersive X-ray spectroscopy (EDS) to evaluate the structural and morphological changes resulting from varying calcination conditions. The XRD analysis confirmed the presence of ZnO in all samples, exhibiting patterns consistent with the JCPDS card of wurtzite ZnO. FESEM observations revealed a correlation between calcination temperature and the morphology of the synthesized ZnO nanostructures. Increasing calcination temperatures and times led to a reduction in the structure thickness, suggesting temperature-dependent alterations in morphology. Furthermore, elemental compositions were determined through EDS analysis, indicating the successful synthesis of ZnO in the samples. The results of this study indicate how different calcination temperature and time affects the structural, morphological, and elemental properties of synthesized ZnO nanostructures. These identified correlations between calcination conditions and structural features provide critical assistance for improving synthesis parameters to obtain specific nanostructure properties. The synthesized ZnO indicates significant potential as a gas sensor material, with substantial effectiveness in detecting volatile organic compounds (VOCs), indicating its usefulness for environmental monitoring and industrial applications. Such insights are critical in directing future research and applications in industries depending on ZnO nanostructures, such as photocatalysis, sensors, and biomedical devices.